A New Way of Life - Peacock, Kimberley (Te Kaharoa, 2020)
Today was the day, I had waited all week for this moment but now that it’s here my nerves are in overdrive. Just last week Dad travelled to Masterton without me and Mum, to make contact with his biological mother. It must have gone well because now we’re all headed off to meet the rest of Dad’s family.